SOURCES, TRANSPORT PATHWAYS, AND ECOLOGICAL IMPACTS OF HEAVY METAL POLLUTION IN AQUATIC ECOSYSTEMS: A NARRATIVE REVIEW - Randi Syafutra (Sylva Jurnal Ilmu-ilmu Kehutanan, 2026)
Persistent heavy metal pollution due to human activities in aquatic ecosystems is an environmental issue affecting ecological balance. This narrative review aims to synthesize scientific literature regarding emission sources, transport pathways, and ecotoxicological impacts of heavy metals. This study employed a narrative review method based on an online literature search focusing on global aquatic ecosystems, analyzing 20 review articles published between 2015 and 2026. The review indicates that heavy metals from industrial waste and agricultural runoff settle in the sediment compartment, which then triggers bioaccumulation in aquatic organisms and poses exposure risks to human food chains. In conclusion, a comprehensive understanding of these pollutant dynamics is deemed essential for designing regulations and remediation strategies to sustainably restore the quality of aquatic resources in the future